Fenomena “No Viral No Justice” Perspektif Teori Penegakkan Hukum - Melinda Dina Gussela; Mila Kurniawati; Jemmy Satria N; Denny Hermanto; Silvanus Fauziansah; Beni Ahmad Saebani (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
The phenomenon of "No Viral No Justice" in Indonesia reflects a shift in the way law is enforced because visibility on social media is one of the measures of legitimacy and urgency of legal action. This study aims to analyze the impact of this phenomenon on the law enforcement system. From the perspective of legal sociology, society has social norms that are used as a measure to law enforcement so various legal events that go viral on social media are part of efforts to law enforcement The viral case is a public pressure that can affect the decisions and responses of law enforcement institutions. Through a normative juridical approach, this study analyzes several cases that have gone viral on social media which play a role in accelerating the legal process and creating a sense of justice in society with significant influence. The findings of this study suggest that while social media can serve as a driver of transparency and accountability, reliance on virality can also pose challenges, such as unfair or reactive law enforcement, and the potential for manipulation of public opinion. Therefore, the phenomenon of "No Viral No Justice" demands a critical evaluation of the relationship between law, society, and technology in Indonesia's law enforcement context.